Calculation of the Ionospheric Cross-Section with the Incoherent Scattering Radar and Its Comparison with the Predictions of the IRI Model - Yasar, Mehmet; Sagir, Selcuk; Emelyanov, Leonid Ya.; Lyashenko, Mykhaylo V.; Korlaelci, Serhat; Atici, Ramazan (Springer, 2023)
The ionosphere is an atmospheric region in which a large number of charged particles interact. Therefore, the production and loss mechanisms in this region play an important role in the modeling and interpretation of the ionosphere. In this study, the cross-section (CS) values, calculated by kinetic theory, were used to validate the International Reference Ionosphere (IRI) model at four different heights (210 km, 240 km, 340 km, and 410 km) on the equinox (March and September) and solstice (June and December) days in 2008 and 2015. The CS values were obtained by using both the temperatures of ions and electrons predicted in the IRI 2007, 2012, and 2016 versions, and the temperatures measured by the Kharkiv incoherent scatter radar (ISR). As a result of the calculation, the CS values in the solar minimum year (in 2008) were greater than those with moderate solar activity in the solar declining phase year (in 2015). The three versions of IRI show almost the same value in 2008. While these values are consistent with the values obtained from the ISR during the day, they are quite low at night. Validation of the model was carried out using Root Mean Square Error (RMSE) and Mean Absolute Percentage Error (MAPE) metrics. According to RMSE and MAPE values, it can be said that the predictions of all three versions of the IRI model are quite good. It can also be stated that the estimations of IRI-2016 are generally better than those of other versions of the IRI model. However, it is important to use ISR data to improve estimations of models at lower altitudes.
Keywords: Cross-section; IRI model; Ionosphere; Incoherent scatter radar